Training on Accounting Recording and Financial Management for PKK Mothers - Devi Febrianti; Ira Megasyara; Amrizal Imawan (Trescode Green Organization, 2026)
Household financial management often appears simple, yet many homemakers struggle to manage it well, particularly in planning expenses and maintaining accounting records. The members of the PKK (Family Welfare Empowerment) group in Deket Wetan Village, Lamongan Regency, generally still record their finances traditionally and have never attended any training on financial planning or financial reporting. This community service activity aimed to provide training on family financial management and simple accounting recording so that participants could better manage household finances and minimize debt incurred to meet daily needs. The activity was conducted over two days at the Deket Wetan Village hall and was followed by one week of intensive mentoring, employing lecture, discussion, and practice methods. Its effectiveness was measured through a pre-test and a post-test. The results showed a positive response and a clear improvement in participants' understanding, with the average score rising from 65 in the pre-test to 87.5 in the post-test, while 70% of participants were able to prepare simple bookkeeping independently. These findings indicate that training in simple financial recording effectively enhances homemakers' knowledge and skills in managing family finances. Continued training and periodic mentoring, supported by the active role of the village government, are recommended so that the acquired knowledge is applied sustainably in daily life.